ECM-algorithms that converge at the rate of EM - Joe Sexton; Anders Rygh Swensen (Statistics Norway, Research Department, 1999)
This paper describes a way of constructing an ECM algorithm such that it converges at the rate of the EM algorithm. The approach is motivated by the well known conjugate directions algorithm, and a special case of it is when the parameters corresponding to different CM steps are orthogonal. Three examples are given illustrating the approach. Possible implications of the theme for the ECME algorithm are briefly discussed.
Keywords: C63; C24; 330; EM algorithm; ECM algorithm; ECME algorithm; missing data; conjugate directions algorithm; orthogonal parameters; rate of convergence.